Research of equivalent and maximum value of noise generated by wind power plants - Butkus, Donatas; Grubliauskas, Raimondas; Mažuolis, Jurgis (Journal of Environmental Engineering and Landscape Management, 2018)
According to the Directive 2009/28EC of European Parliament and Council, dated April 23, 2009, Lithuania should strive for the part of renewable energy sources in the balance of electric energy to reach no less than 23% in the year 2020. The most favorable condition for development of wind energy in Lithuania is on a 50 km width zone by the seaside. Parks of wind power plants are expanding fast, but there is a lack of data about noise generated by wind turbines. The noise generated by the wind power plants is known to fluctuate and may spread up to 2 km beyond the wind power park. Research of noise generated by wind power plants was performed in the western part of Lithuania, near Rudaiciai village (Kretinga district) at the park of four wind power plants. Measurements were performed in cold and warm seasons when different wind speed, environment humidity and air temperatures dominated. The sound pressure levels of noise generated by wind power plants were established. The noise spread in the wind parks and beyond was evaluated according to hygiene norm HN 33:2007 “Acoustic noise. Noise value limits in the residential and public buildings and their surroundings”. Article in English. Vėjo jėgainių skleidžiamo triukšmo ekvivalentinių ir didžiausių verčių tyrimai Santrauka. Remiantis Europos Sajungos Parlamento ir Tarybos 2009 m. balandžio 23 d. direktyva 2009/28/EB Lietuva turi siekti, kad 2020 m. atsinaujinančiųjų energijos išteklių dalis šalies elektros energijos balanse sudarytų ne mažiau kaip 23%. Lietuvoje vėjo energetikai plėtoti palankiausios sąlygos yra maždaug 50 km pločio juosta prie jūros pakrantės. Sparčiai plečiantis vėjo jėgainių parkams trūksta duomenų apie vėjo jėgainių skleidžiamą triukšmą. Žinoma, kad triukšmas nuo vėjo jėgainių yra fliuktuojantis bei gali sklisti iki 2 km už vėjo jėgainių parko ribų. Vėjo jėgainių skleidžiamo triukšmo tyrimai buvo atliekami vakarų Lietuvoje, Rūdaičių k. (Kretingos r.) prieigose esančiame keturių vėjo jėgainių parke. Atlikti žiemos ir vasaros matavimai, vyraujant skirtingiems vėjo greičiams, aplin-kos oro drėgniui, oro temperatūrai. Nustatyti vėjo jėgainių parko skleidžiamo triukšmo, garso slėgio lygiai. Pagal higienos normą HN 33:2007 , Akustinis triukšmas. Triukšmo ribiniai dydžiai gyvenamuosiuose ir visuomeninės paskirties pastatuose bei jų aplinkoje“ įvertinta triukšmo sklaida vėjo jėgainių pake ir už jo ribų. Reikšminiai žodžiai: triukšmas, vėjo jėgainė, vėjo jėgainių parkas Исследование эквивалентных и максимальных зна чений шума, распространяемого ветряными установками Резюме. На основании Директивы 2009/28/УС, принятой 23 апреля 2009 г. Парламентом и Советом Евросоюза, Литва должна стремиться к тому, чтобы к 2020 г. часть возобновляемых источников энергии в электроэнергетическомбалансе страны составляла по крайней мере 23%. В Литве наиболее благоприятные условия для полученияветряной энергии могут быть созданы на полосе шириной примерно в 50 км вдоль зоны морского побережъя. В связи с интенсивным развитием парков ветряных установок данных о создаваемом ими шуме не достаточно.Известно, что шум от ветряных турбин флуктирует и может распространяться до 2 км за пределы парковветряных установок. Исследования четырех ветряных турбин и создаваемого ими шума проводились в парке ветряных установок на Западе Литвы, в Рудайчяй (Кретингский район). Измерения проводились зимой и летом при разной скорости ветра, влажности и температуре воздуха. Установлены уровни распространяемого ветряными установками шумаи звукового давления. На основании гигиенической нормы HN 33:2007 «Акустический шум. Предельныевеличины шума для жилых зданий, зданий общественного назначения и их среды» установлено распространениешума в парке ветряных установок и за его пределами. Ключевые слова: шум, ветряная турбина, парк ветряных установок